A Comparative Study of UCS Results Obtained from Triaxial Tests Under Multiple Failure State Conditions (Test Type II) - Nghia Quoc Trinh; Eivind Grøv; Gunnar Vistnes (Applied Sciences)
In any rock engineering project, the uniaxial compressive strength (UCS) is one of the most relevant parameters to be determined as it is used for a variety of purposes. Traditionally, the UCS of a rock sample is obtained by carrying out a uniaxial test on a rock core. The UCS can also be estimated indirectly by correlating it with different parameters such as the pulse velocity (Vp), Schmidt hammer rebound number (Rn), effective porosity (ne), total porosity (nt), dry density (γd), point load index (Is50), shear wave velocity (Vs), Brazilian tensile strength (BTS), slake durability index (SDI), or by using an artificial neural network (ANN). This paper presents a comparative study for an additional approach to determine the UCS, namely by converting triaxial test results to the UCS. This research has been conducted to encourage further utilisation of laboratory test results obtained from triaxial tests. Triaxial tests are normally performed to determine the intact rock strength envelope. By further utilisation of triaxial test data to estimate the UCS, the database of the UCS can be enriched for rock engineering projects. The method can also be used in cases of limited samples or when samples are too challenged for carrying out a USC test. The research showed that the UCS derived by this method is more direct and more accurate than many empirical methods. Furthermore, the test procedure described herein (carrying out the UCS and triaxial tests on the same sample) can be used to evaluate the accuracy of the calculated UCS. It is important to bear in mind that the scope of this study is not to develop a new method or replace the traditional uniaxial compression test with the method presented in this paper. The purpose and intention is to document that the test results obtained from triaxial testing can be utilised to also provide values of UCS from the same samples.